Diversity of Biodeteriorative Bacterial and Fungal Consortia in Winter and Summer on Historical Sandstone of the Northern Pergola, Museum of King John III’s Palace at Wilanow, Poland - Magdalena Dyda; Agnieszka Laudy; Przemyslaw Decewicz; Krzysztof Romaniuk; Martyna Ciezkowska; Anna Szajewska; Danuta Solecka; Lukasz Dziewit; Lukasz Drewniak; Aleksandra Skłodowska (Applied Sciences, 2021)
The aim of the presented investigation was to describe seasonal changes of microbial community composition in situ in different biocenoses on historical sandstone of the Northern Pergola in the Museum of King John III’s Palace at Wilanow (Poland). The microbial biodiversity was analyzed by the application of Illumina-based next-generation sequencing methods. The metabarcoding analysis allowed for detecting lichenized fungi taxa with the clear domination of two genera: Lecania and Rhinocladiella. It was also observed that, during winter, the richness of fungal communities increased in the biocenoses dominated by lichens and mosses. The metabarcoding analysis showed 34 bacterial genera, with a clear domination of Sphingomonas spp. across almost all biocenoses. Acidophilic bacteria from Acidobacteriaceae and Acetobacteraceae families were also identified, and the results showed that a significant number of bacterial strains isolated during the summer displayed the ability to acidification in contrast to strains isolated in winter, when a large number of isolates displayed alkalizing activity. Other bacteria capable of nitrogen fixation and hydrocarbon utilization (including aromatic hydrocarbons) as well as halophilic microorganisms were also found. The diversity of organisms in the biofilm ensures its stability throughout the year despite the differences recorded between winter and summer.